Slurry erosion behaviour of carbon/epoxy quasi-isotropic laminates based on Taguchi's optimization method. (May 2021) - Padmaraj, N.H.; Vijaya, Kini M.; Shreepannaga; Amritha, U.; Dayananda, Pai
Highlights: Experimental investigations on the slurry erosion performance of the CFRP laminates. Studies conducted by varying rotational speed, angle and slurry concentration. Erosion process mainly influenced by angle of rotation and rotational speed. Abstract: Erosion of composite structure due to i nteraction with slurry and water debris is one of the major challenges faced by the marine industries. The present work focuses on studying the influence of specimen angle of rotation, slurry concentration and rotational speed on erosion behaviour of carbon/epoxy quasi-isotropic laminates. Specimens were fabricated using prepreg and autoclave curing process. Experiments were conducted in a slurry pot erosion test rig using sea sand particles as erodent material. Taguchi L27 array is used to analyse the effect of selected factors on the erosion. Morphology of the eroded surfaces was examined using a scanning electron microscope to study the erosion behaviour. It is observed that rotational speed and angle of rotation have a significant influence on the erosion behaviour and maximum erosion observed at a rotational angle of 15° and the nature of erosion process can be categorized into semi ductile erosion behaviour. Experiments conducted at a testing condition of 1500 RPM, 70% slurry concentration and 15° of rotational angle showed maximum mass loss.